2010
DOI: 10.3171/2009.7.jns0989
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after complete surgical removal of giant vestibular schwannomas

Abstract: In patients with a giant VS, total tumor removal can be achieved via the retrosigmoid approach with a 0% mortality rate and low morbidity rate, especially with regards to facial nerve function. In selected cases even hearing preservation is possible. Tumor size significantly correlates with postoperative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
204
2
20

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(239 citation statements)
references
References 42 publications
(87 reference statements)
13
204
2
20
Order By: Relevance
“…Variations in surgical approach, staging of tumor resection, and postoperative radiosurgery have been proposed to achieve superior results while respecting the need for maximal tumor resection, brainstem decompression, facial nerve preservation, and long-term tumor remission. 1,9,14,30,34 The literature clearly demonstrates the superiority of the standard retrosigmoid or translabyrinthine approaches in preserving facial nerve function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in surgical approach, staging of tumor resection, and postoperative radiosurgery have been proposed to achieve superior results while respecting the need for maximal tumor resection, brainstem decompression, facial nerve preservation, and long-term tumor remission. 1,9,14,30,34 The literature clearly demonstrates the superiority of the standard retrosigmoid or translabyrinthine approaches in preserving facial nerve function.…”
Section: Discussionmentioning
confidence: 99%
“…36 Studies have shown that the best strategy for tumor control is to achieve a high level of tumor resection while being mindful of facial nerve function. 41 A single-institution series from Samii et al 34 showed that of 50 patients with large vestibular schwannomas treated with gross-total resection, 92% had anatomical preservation of the facial nerve. At their last follow-up, 75% of patients had excellent or good facial nerve function, 19% had fair function, and 6% had poor function.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,28 In addition to CN involvement, larger tumors compress and displace the brainstem, distorting the usual view of the brain-tumor interface; draining veins in large and giant tumors may be unusually distended and fragile, increasing the risk of hemorrhage. 25 When tumors are stratified by size, those larger than 3 cm (20%-22%) are associated with higher complication rates and longer hospital stays than those under 3 cm (6%-9.6%). 28 In our series, no mortality or unexpected adverse neurological events were encountered.…”
Section: Sizementioning
confidence: 99%
“…13,75 Tumor size is not correlated with the risk of CSF fistula, 69 although larger tumors approached through the translabyrinthine route may be associated with a higher CSF leak rate. 58,75 This could also be related to the approach itself, as meticulous dural closure is difficult, if not impossible, with this technique. The present analysis confirms the belief that the retrosigmoid approach may result in a greater risk of CSF leakage than the middle cranial fossa and translabyrinthine approaches, which we did not find to differ significantly from each other in this respect.…”
Section: Postoperative Csf Leakagementioning
confidence: 99%
“…11,75 Frequently cited predictors of facial nerve function include tumor size, surgical approach, and the use of intraoperative monitoring. 15,22,40,64,75 The length of contact of the tumor with the nerve has also been suggested as a potential prognostic factor. 18 Samii et al 74 believe that prior surgery or radiosurgery and the presence of an intratumoral cyst are negative predictors of postoperative facial nerve function.…”
Section: Facial Nerve Functionmentioning
confidence: 99%